Effect of Sendai Virus Infection on Lipid Metabolism in Chick Embryo Fibroblasts - Blair, Carol D. (1972)
Lipid metabolism in the “abortive” system, Sendai virus-infected primary chick embryo fibroblasts, was examined by using (32)P-orthophosphate, (14)C-glucose, and (14)C-glycerol as precursors. Incorporation of radioactivity from (32)P-orthophosphate and (14)C-glucose into lipid was increased in infected cells. Synthesis of all individual phospholipids was about equally stimulated. There was also evidence for increased lipid synthesis in more productively infected monkey kidney cells. Incorporation of (14)C-glycerol when at a high level in the medium was also increased. However, when this precursor was supplied in minute quantities of high specific activity, incorporation was inhibited. Even though incorporation of radioactivity from (14)C-glucose was stimulated during long labeling periods, the uptake of this precursor during short pulses was inhibited in infected cells. The phenomenon of increased labeling of triglyceride in infected chick cells under certain conditions is discussed, in conjunction with the other effects, in terms of related changes in other virus-infected systems.